The Implications of the Anglo-Dutch Treaty of 1824 on the Demarcation and Economy of Sebatik Island (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This paper discusses the implications that happened to the borders and economy of Sebatik Island as a result of the Treaty of London on March 17, 1824, involving two colonial powers, namely the British and the Dutch. This agreement, known as an oath of allegiance, is also called the Anglo-Dutch Treaty (1824), which resolved the dispute between the British and the Dutch in the Anglo-Dutch Treaty (1814). The agreements involving these two great powers indirectly had implications on their respective colonies at that time. This great impact resulted in the Malay Islands being divided into two spheres of influence, namely the British influence and the Dutch influence. Eventually, there was a split involving the Johor-Riau Empire, when Singapore and the Mainland of Johor fell under British rule, while the Riau Islands were under Dutch rule. Although this agreement seemed to give complete satisfaction to the two colonial powers, it was not able to end the competition that existed between the two said powers. On the contrary, as a result of this agreement, the British and the Dutch were seen to compete more fiercely in having colonies. This was what happened on an island in the northern part of Borneo, bordering East Kalimantan (now North Kalimantan), known as Sebatik Island. Sebatik Island received direct implications due to the dividing line involving the island, as outlined in the Treaty of London of 1824. The study carried out shows that the straight line of the border still remains until today, involving two national entities, namely Malaysia and Indonesia. This study uses qualitative methods. The information is obtained from previous studies, official documents such as files and microfilms, as well as The Colonial Office (CO), Foreign Office (FO) and North Borneo Central Archive (NBCA) in the State Archives of Sabah. The findings show that the London Treaty of 1824 had a direct impact on the people of Sebatik Island, starting after the end of Western colonization in Malaysia in 1963 and in Indonesia in 1945. Therefore, this paper dissects the factors that led to the Treaty of London of 1824, and the effect on the border and economy of Sebatik Island. Full text: PDF